Production by cultured human monocytes of mesangial cell proliferation factor(s) differing from interleukin-1 and interleukin-6. - Morioka, T (1991)
Conditioned media from human peripheral blood leucocytes treated with lipopolysaccharide (LPS) induced a marked increase in the 3H-thymidine incorporation of cultured mesangial cells at low serum concentration (four to six times higher than control). Two sizes (100-70 and 8-12 kD) of monocyte-derived mesangial cell proliferating factors (MDF) were separated by column chromatography. Their peaks were distinct from those of thymocyte proliferating activity. The addition of anti-human interleukin-1 (IL-1) or anti-recombinant human interleukin-6 (IL-6) antibody to the fractionated MDF failed to have any effect on the mitogenic activity toward mesangial cells. The addition of anti-human platelet-derived growth factor (PDGF) antibody to the low molecular weight fraction decreased mesangial cell mitogenic activity (40-60% of control), but addition to the higher fraction did not (80-100% of control). From these data it seems that a large portion of the monocyte-derived mesangial cell growth factor was not comprised of IL-1 or IL-6 but of PDGF-like molecules; and that there is an unknown mesangial cell proliferating factor (or factors) besides IL-1, IL-6 and PDGF.